Reflecting on Modern Sport in Ancient Olympia Proceedings of the 2016 Meeting of the International Association for the Philosophy of Sport at the International Olympic Academy - Reid, Heather L. (Parnassos Press - Fonte Aretusa, 2017)
Pindar called Olympia "Queen of truth," so it was appropriate that nearly 100 philosophers of sport from 18 countries on four continents presented 80 different papers there in September of 2016. This proceedings gathers fourteen of them, including two of the keynotes. Topics range from sport in education to transgender athletes to Taijiquan.